HAMBATAN DAN PELUANG PEMANFAATAN E-COMMERCE UNTUK PERDAGANGAN INTERNASIONAL PADA USAHA KECIL MENENGAH DI DEPOK JAWA BARAT - Lindiawatie, Lindiawatie; Shahreza, Dhona (Develop, 2024)
The current phenomenon is that few small and medium-sized enterprises contribute to international trade. Meanwhile, advances in information communication technology can be a marketing tool that is able to reach the territorial boundaries of a country that has not been utilized optimally by small and medium businesses. This research wants to inform the problems and involvement of SMEs in international trade e-commerce. The purpose of the study is to describe SMEs in Depok that utilize e-commerce for export purposes and to find out the obstacles and opportunities of SMEs in Depok in utilizing e-commerce for export purposes. The research was conducted in the city of Depok, West Java. The research method used is a qualitative descriptive phenomenology method. Data collection by conducting structured interviews with SMEs through the distribution of questionnaires to four small and medium enterprises recommended by the Depok Regional Government. The results of the study found that small and medium enterprises in Depok, West Java have not taken advantage of international trade e-commerce for export purposes because they face several obstacles, namely limited knowledge about export e-commerce, limited labor that masters export e-commerce, inability to provide partners according to e-commerce requirements abroad, inability to update information continuously (website administration) and inability to serve consumer demand at all times due to time zone differences. Meanwhile, opportunities in the use of e-commerce for export purposes will arise from the policy of internationalizing SME products, the government's strategy to encourage exports with e-commerce and digital literacy training for SMEs. This is a positive opportunity for SMEs to improve their ability to utilize international trade e-commerce for export purposes. The government needs to find solutions to obstacles for SMEs in the use of international trade e-commerce for export purposes. This research proves that the digitalization of SMEs for export purposes has not been optimally programmed.